Tungsten fiber toughened tungsten composite material and preparation method thereof
The sintering process of preparing metal oxide-encapsulated tungsten powder and tungsten fibers through chemical method solves the problem of difficult adjustment of the interface bonding strength between tungsten fiber and tungsten matrix, and realizes the efficient mechanical properties of composite materials and the suitability of industrial production.
Patent Information
- Application Number
- CN202411628534.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing tungsten fiber toughened tungsten composite materials, the interface bonding strength between the tungsten fiber and the tungsten matrix is difficult to adjust, resulting in a decrease in the mechanical properties of the material and abnormal recrystallization of the fiber surface.
The metal oxide-encapsulated tungsten powder was prepared by chemical method, mixed with tungsten fibers and sintered to form a tungsten fiber toughened tungsten composite material, optimizing the interface bonding strength between the fiber and the matrix and avoiding abnormal recrystallization.
It effectively improves the density and mechanical properties of composite materials, and can still exert the toughening effect of fibers at high temperatures, and is suitable for industrial production.
Smart Images

Figure CN119457059A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a tungsten fiber toughened tungsten composite material and a preparation method thereof. Background Art
[0002] In response to various problems such as recrystallization brittleness, low-temperature brittleness and irradiation brittleness of tungsten materials, researchers mainly use grain refinement, alloying, fiber toughening and layered toughening to improve them. Tungsten fiber toughened tungsten composites are a typical fiber toughening method. Its toughening phase is tungsten fiber produced by drawing process, which has high strength. Compared with heterogeneous materials such as carbon fiber, tungsten fiber and tungsten matrix are homologous and will not introduce other impurities, which is conducive to maintaining the purity and thermoelectric properties of the composite material. However, the connection between the fiber and the matrix has always limited the further application of this material. If the interface bonding strength is too high, the tungsten fiber and the tungsten matrix will be bonded together and cannot play the role of the fiber; if the interface bonding strength is too low, the density of the composite material cannot be guaranteed and the mechanical properties will decrease. In addition, the direct connection between tungsten fiber and tungsten matrix will also cause abnormal recrystallization on the fiber surface, deteriorating the material properties. Related studies have proposed to improve the interface bonding by coating the fiber surface or directly doping alloy particles in the tungsten matrix. However, the former has greater process difficulty and is not suitable for industrial production; while the latter has uneven particle distribution, which affects the toughening effect.
[0003] The Chinese patent application document with publication number CN 114959518 A discloses a tungsten fiber, Y 2 O 3 Nanoparticles synergistically toughened tungsten-based composites, including tungsten fibers, Y 2 O 3 Nanoparticles and tungsten powder, the length of the tungsten fiber is 1-3 mm, the diameter is 100-200 μm, the mass proportion of tungsten fiber is 30-50%; the particle size of tungsten powder is 1 μm, 5 μm, 25 μm, and the mass proportion of each particle size is 3:1:6; Y 2 O 3 The mass percentage of nanoparticles is 0.5-2%. 2 O 3 Nanoparticles refine the grains, avoid the complete connection between tungsten fiber and tungsten matrix at high temperature, weaken the bonding strength between tungsten matrix and tungsten fiber, and make the interface between tungsten fiber and tungsten matrix crack during the fracture process, promote the plastic deformation of tungsten fiber, play a better bridging role, effectively play the toughening effect of W fiber, and can play a strengthening role, but it needs to be matched with tungsten powder of different particle sizes to achieve the desired effect, and is not suitable for tungsten powder matrix of single particle size. In addition, a single doping and mixing method will also affect Y 2 O 3 Uniform distribution in the tungsten matrix reduces its performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is how to adjust the interface relationship between tungsten fiber and tungsten matrix in tungsten fiber reinforced tungsten composite material, control the interface bonding strength between the two, and improve the comprehensive performance of the composite material.
[0005] The present invention solves the above technical problems through the following technical means:
[0006] A tungsten fiber toughened tungsten composite material, the raw materials of which include, by mass percentage, 70-90% of tungsten powder wrapped with metal oxide and 10-30% of tungsten fiber.
[0007] Preferably, the tungsten powder coated with metal oxide is Y 2 O 3 Wrapped tungsten powder, ZrO 2 One or a mixture of two of the encapsulated tungsten powders.
[0008] Preferably, the tungsten fiber has a length of 2.5 to 5 mm and a diameter of 50 to 300 μm.
[0009] Preferably, the particle size of the tungsten powder coated with the metal oxide is 2 to 5 μm, and the thickness of the metal oxide coating is 0.1 to 0.3 μm.
[0010] Preferably, the method for preparing the tungsten powder coated with metal oxide comprises the following steps: dissolving the metal salt and the surfactant in water respectively, adding the obtained two solutions to the solution containing ammonium metatungstate, adding oxalic acid, heating and stirring to volatilize the solvent, and then heating and stirring to volatilize the solvent. 2 The tungsten powder coated with the metal oxide is obtained by reduction under the atmosphere.
[0011] The present invention also provides a method for preparing the tungsten fiber toughened tungsten composite material, comprising the following steps:
[0012] S1: Powder preparation: Preparation of tungsten powder coated with metal oxide by chemical method;
[0013] S2: powder mixing: mixing tungsten fiber and prepared tungsten powder coated with metal oxide to obtain a mixture;
[0014] S3: Sintering: putting the mixed material obtained in S2 into a mold, and sintering to obtain the tungsten fiber toughened tungsten composite material.
[0015] The tungsten fiber-reinforced tungsten composite material prepared by the present invention utilizes a chemical method to wrap oxide particles around a tungsten matrix and is very stable during high-temperature sintering, effectively improving the connection between the fiber and the matrix, avoiding direct contact between the tungsten fiber and the tungsten matrix, optimizing the interface bonding strength between the two, avoiding the occurrence of abnormal recrystallization and the like, and promoting density while enabling the composite material to still exert the toughening effect of the tungsten fiber at high temperatures.
[0016] Preferably, S1 specifically comprises the following steps: dissolving the metal salt and the surfactant in water respectively, adding the obtained two solutions to the solution containing ammonium metatungstate, adding oxalic acid, heating and stirring to volatilize the solvent, and then heating and stirring to volatilize the solvent. 2 The tungsten powder coated with the metal oxide is obtained by reduction under the atmosphere.
[0017] Preferably, the metal salt is yttrium nitrate, zirconium nitrate or a mixture of the two.
[0018] Preferably, the surfactant is triethanolamine.
[0019] Preferably, the mass ratio of the metal salt to the surfactant is 1:2; the mass of the oxalic acid is 38% of the mass of ammonium metatungstate; and the mass ratio of the metal salt to ammonium metatungstate is 22-75:55-92.
[0020] Preferably, the sintering pressure is 20-40 MPa, and the insulation temperature is 1400-1700°C.
[0021] Preferably, in S2, the mixing time is 2 to 4 hours.
[0022] The advantages of the present invention are:
[0023] (1) The present invention prepares tungsten powder wrapped by metal oxide particles by a chemical method, thereby avoiding direct contact between the tungsten fiber and the tungsten matrix during high-temperature sintering, optimizing the interface bonding strength between the two, inhibiting the generation of abnormal recrystallization on the fiber surface, and maintaining good toughness of the composite material.
[0024] (2) Compared with direct tungsten fiber coating, the present invention adopts a chemical method to prepare composite powder. The composite material obtained by sintering has the same effect, and no abnormal recrystallization occurs. It is more stable at high temperature and will not cause the oxide film to be damaged. The powder making process is suitable for large-scale industrial production, and the raw materials are cheap and easy to obtain, which is more economical.
[0025] (3) Compared with directly doping oxide particles, the present invention adopts a chemical method to prepare the composite powder, so that the oxide particles are attached to the tungsten matrix, the composition is more uniform, and the comprehensive mechanical properties of the composite material can be effectively improved while refining the grains. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is W in Example 1 of the present invention f -Y 2 O 3 Schematic diagram of the structure of / W composite material;
[0027] Figure 2 This is a morphological image of tungsten particles wrapped by metal oxide particles in the tungsten fiber-toughened tungsten composite material of Example 1 of the present invention;
[0028] Figure 3 This is a metallographic structure diagram of the tungsten fiber toughened tungsten composite material according to Example 2 of the present invention;
[0029] Figure 4 WY obtained in Example 3 of the present invention 2 O 3 Energy spectrum image of composite powder;
[0030] Figure 5 This is a metallographic structure diagram of the tungsten fiber toughened tungsten composite material of Comparative Example 1 of the present invention;
[0031] Figure 6 It is a three-point bending performance test diagram of the tungsten fiber toughened tungsten composite material of Comparative Examples 1-2 and Example 3 of the present invention;
[0032] Figure 7 This is a metallographic image of the interior of the composite material obtained by directly doping the mixed powder in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0035] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0036] Example 1
[0037] This embodiment provides a method for preparing a tungsten fiber toughened tungsten composite material. 2 O 3 Composite powder (ie metal oxide Y 2 O3 The weight of the wrapped tungsten powder is 90%, the length of the tungsten fiber is 3 mm, the diameter is 50 μm, and the weight of the tungsten fiber is 10%. The specific preparation method includes the following steps:
[0038] (1) Powder making: 22.1 g of yttrium nitrate (Y(NO 3 ) 3 6H 2 200 ml of deionized water, and 44.2 g of surfactant triethanolamine were dissolved in 200 ml of deionized water, stirred evenly, and the two solutions were poured into a mixture containing 91.8 g of ammonium metatungstate (H 28 N 6 O 41 W 12 ) in an aqueous solution; then adding an oxalic acid aqueous solution, stirring at 120°C until the liquid is completely volatilized to obtain a block precursor, drying and grinding to obtain a precursor powder; placing the precursor powder in a tube furnace, passing H at 1000°C 2 Reduction for 2h gave metal oxide Y 2 O 3 WY 2 O 3 Composite powder. The amount of oxalic acid added is 38% of the mass of ammonium metatungstate;
[0039] (2) Mixed powder: 90g WY 2 O 3 The composite powder and 10 g of tungsten fiber were mixed in a drum mixer for 2 hours.
[0040] (3) Sintering: The mixed powder is placed in a mold and sintered by spark plasma sintering. During the sintering process, the heating rate is 100°C / min, the temperature is raised to 1400°C, and the temperature is kept for 5 minutes. The sintering pressure is 20MPa. After furnace cooling, a tungsten fiber toughened tungsten composite material sample is obtained, which is denoted as W f -Y 2 O 3 / W.
[0041] Figure 1 This is a schematic diagram of the structure of the prepared tungsten fiber-toughened tungsten composite material, where the cylinder is the sintered sample, the blue circle represents the tungsten particles, the green strips represent the tungsten fibers, and the red clumps represent the oxide film on the surface of the tungsten particles.
[0042] Figure 2 The prepared composite material W f -Y 2 O 3 / W transmission image, it can be seen that Y is formed in the tungsten matrix 2 O 3 The encapsulated tungsten particles have a particle size of 2 to 5 μm, Y2 O 3 The wrapping thickness is 0.1 to 0.3 μm, isolating the direct contact with the fiber.
[0043] Example 2
[0044] This embodiment provides a method for preparing a tungsten fiber toughened tungsten composite material. 2 Composite powder (ie metal oxide ZrO 2 The weight of the wrapped tungsten powder is 70%; the length of the tungsten fiber is 5mm, the diameter is 300μm, and the weight of the tungsten fiber is 30%. The specific preparation method includes the following steps:
[0045] (1) Powder making: 70.7 g zirconium nitrate (Zr(NO 3 ) 4 ·5H 2 200 ml of deionized water were used to dissolve 141.4 g of triethanolamine and 59.4 g of ammonium metatungstate (H 28 N 6 O 41 W 12 ) in an aqueous solution; then add an appropriate amount of oxalic acid aqueous solution, stir at 120°C until the liquid is completely volatilized to obtain a bulk precursor, dry and grind the bulk precursor to obtain a precursor powder. Place the precursor powder in a tube furnace and pass H at 1000°C. 2 After reduction for 2 h, metal oxide ZrO was obtained. 2 Encapsulated tungsten powder, namely W-ZrO 2 Composite powder, wherein the amount of oxalic acid added is 38% of the mass of ammonium metatungstate.
[0046] (2) Mixing powder: 70g W-ZrO 2 The composite powder and 30 g of tungsten fiber were mixed in a drum mixer for 4 hours.
[0047] (3) Sintering: The mixed powder is placed in a mold and sintered by spark plasma sintering. During the sintering process, the heating rate is 100°C / min, the temperature is raised to 1700°C, and the temperature is kept for 5 minutes. The sintering pressure is 40MPa. After furnace cooling, a tungsten fiber toughened tungsten composite material sample is obtained, which is denoted as W f -ZrO 2 / W.
[0048] Figure 3 The prepared composite material W f -ZrO 2 / W metallographic structure, it can be seen that the fiber has not been recrystallized and is well bonded to the tungsten matrix without obvious holes.
[0049] Example 3
[0050] This embodiment provides a method for preparing a tungsten fiber toughened tungsten composite material. 2 O 3 Composite powder (ie metal oxide Y 2 O 3 The weight of the wrapped tungsten powder is 80%; the length of the tungsten fiber is 2.5mm, the diameter is 100μm, and the weight of the tungsten fiber is 20%. The specific preparation method includes the following steps:
[0051] (1) Powder making: 22.1 g of yttrium nitrate (Y(NO 3 ) 3 6H 2 200 ml of deionized water, and 44.2 g of triethanolamine were dissolved in 200 ml of deionized water, stirred evenly, and the two solutions were poured into a mixture containing 81 g of ammonium metatungstate (H 28 N 6 O 41 W 12 ) in an aqueous solution; then adding an oxalic acid aqueous solution, stirring at 120°C until the liquid is completely volatilized to obtain a bulk precursor, drying and grinding the bulk precursor to obtain a precursor powder; placing the precursor powder in a tube furnace, passing H at 1000°C 2 Reduction for 2h gave metal oxide Y 2 O 3 WY 2 O 3 Composite powder, wherein the amount of oxalic acid added is 38% of the mass of ammonium metatungstate.
[0052] (2) Mixed powder: 80g WY 2 O 3 The composite powder and 20 g of tungsten fiber were mixed in a drum mixer for 3 hours.
[0053] (3) Sintering: The mixed powder is placed in a mold and sintered by spark plasma sintering. During the sintering process, the heating rate is 100°C / min, the temperature is raised to 1600°C, and the temperature is kept for 5 minutes. The sintering pressure is 40MPa. After furnace cooling, a tungsten fiber toughened tungsten composite material sample is obtained.
[0054] Figure 4 The prepared WY 2 O 3 Energy spectrum image of composite powder, we can see Y 2 O 3 Evenly distributed on the tungsten particles.
[0055] Comparative Example 1
[0056] This comparative example provides a conventional tungsten fiber toughened tungsten composite material, the particle size of tungsten powder is 5μm, the mass proportion of tungsten powder is 80%, the length of tungsten fiber is 2.5mm, the diameter is 100μm, and the mass proportion of tungsten fiber is 20%. The specific preparation method includes the following steps:
[0057] (1) Powder mixing: 80 g of tungsten powder and 20 g of tungsten fiber were placed in a drum mixer and mixed for 3 hours.
[0058] (2) Sintering: The mixed powder is placed in a mold and sintered by spark plasma sintering. During the sintering process, the heating rate is 100℃ / min, the temperature is raised to 1600℃, and the temperature is kept for 5 minutes. The sintering pressure is 40MPa. After the furnace is cooled, the sample is obtained and is recorded as W. f / W.
[0059] Figure 5 For the preparation of W f From the metallographic structure of the tungsten / W composite material, it can be seen that a circle of recrystallization has occurred outside the fiber, and there are certain holes inside the tungsten matrix, with poor density.
[0060] Comparative Example 2
[0061] A method for directly doping oxide particles is provided in a Chinese patent application document with publication number CN114959518A, but the desired effect needs to be achieved through a ratio of large and small particle sizes, and direct doping of mixed powders is prone to uneven oxide particles.
[0062] The tungsten powder with a particle size of 5 μm was directly doped with Y2O3 accounting for 2% of the mass of the tungsten powder. 2 O 3 Get tungsten powder and Y 2 O 3 A mixture of Y 2 O 3 The total mass of tungsten powder accounts for 80%, the length of tungsten fiber is 2.5mm, the diameter is 100μm, and the mass of tungsten fiber accounts for 20%. The specific preparation method includes the following steps:
[0063] (1) Mixing powder: Mix 80g of tungsten powder and Y 2 O 3 The mixture and 20 g of tungsten fiber were put into a drum mixer and mixed for 3 hours.
[0064] (2) Sintering: The mixed powder is placed in a mold and sintered by spark plasma sintering. During the sintering process, the heating rate is 100°C / min, the temperature is raised to 1600°C, and the temperature is kept for 5 minutes. The sintering pressure is 40 MPa. After the furnace is cooled, the sample is obtained.
[0065] Figure 6The comparison of the three-point bending performance test of the materials prepared in Example 3 and Comparative Examples 1 and 2 shows that the composite material prepared by sintering the tungsten particles wrapped with oxides has obvious pseudo-toughness and a higher elongation. Comparative Example 1 shows obvious brittleness; while Comparative Example 2 has improved toughness, but relatively low strength. This may be due to the direct doping of Y 2 O 3 The uneven particle distribution leads to low density of the composite material. Figure 7 This is a metallographic image of a composite material prepared by directly doping oxide particles with mixed powder. It can be seen that Y exists inside the tungsten matrix. 2 O 3 Large particles.
[0066] In the case of containing a small amount of fibers, Examples 1 to 3 of the present invention can still exert the fiber toughening effect to the maximum extent, which is attributed to the composite powder of tungsten particles wrapped with oxides prepared by a chemical method.
[0067] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A tungsten fiber toughened tungsten composite material, characterized in that: The raw materials include, by mass percentage, 70-90% of tungsten powder wrapped with metal oxide and 10-30% of tungsten fiber.
2. The tungsten fiber toughened tungsten composite material according to claim 1, characterized in that: The metal oxide coated tungsten powder is one of Y2O3 coated tungsten powder and ZrO2 coated tungsten powder or a mixture of the two.
3. The tungsten fiber toughened tungsten composite material according to claim 1, characterized in that: The length of the tungsten fiber is 2.5-5 mm, and the diameter is 50-300 μm.
4. The tungsten fiber toughened tungsten composite material according to any one of claims 1 to 3, characterized in that: The particle size of the tungsten powder coated with the metal oxide is 2-5 μm, and the thickness of the metal oxide coating is 0.1-0.3 μm.
5. A method for preparing a tungsten fiber toughened tungsten composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Powder preparation: Preparation of tungsten powder coated with metal oxide by chemical method; S2: powder mixing: mixing tungsten fiber and prepared tungsten powder coated with metal oxide to obtain a mixture; S3: Sintering: putting the mixed material obtained in S2 into a mold, and sintering to obtain the tungsten fiber toughened tungsten composite material.
6. The method for preparing the tungsten fiber toughened tungsten composite material according to claim 5, characterized in that: S1 specifically includes the following steps: dissolving a metal salt and a surfactant in water respectively, adding the obtained two solutions into a solution containing ammonium metatungstate, adding oxalic acid, heating and stirring to volatilize the solvent, and then reducing under a H2 atmosphere to obtain the tungsten powder coated with the metal oxide.
7. The method for preparing the tungsten fiber toughened tungsten composite material according to claim 6, characterized in that: The metal salt is one of yttrium nitrate and zirconium nitrate or a mixture of the two.
8. The method for preparing a tungsten fiber toughened tungsten composite material according to claim 6, characterized in that: The surfactant is triethanolamine.
9. The method for preparing a tungsten fiber toughened tungsten composite material according to claim 6, characterized in that: The mass ratio of the metal salt to the surfactant is 1:2; the mass of the oxalic acid is 38% of the mass of ammonium metatungstate; the mass ratio of the metal salt to ammonium metatungstate is 22-75:55-92.
10. The method for preparing a tungsten fiber toughened tungsten composite material according to any one of claims 5 to 9, characterized in that: The sintering pressure is 20-40 MPa, and the insulation temperature is 1400-1700°C.
Citation Information
Patent Citations
Tungsten-based plasma facing material and preparation method thereof
CN102560292A
Method for improving sintering compactness of W-Y2O3 composite material
CN109735735A
High-hardness composite oxide dispersion strengthened ODS tungsten alloy and preparation method thereof
CN112011703A
Tungsten-based composite material synergistically toughened by tungsten fibers and oxide nanoparticles and preparation method of tungsten-based composite material
CN114959518A
Tungsten and molybdenum fiber reinforced composite, its production, and part for high temperature service using the composite
JP2000096180A